Upside-Down and Backwards: Time Discipline in a Canadian Inuit Town - Stern, Pamela (Anthropologica, 2022)
Time discipline is a potent, but often hidden social force. This paper considers issues of time discipline and temporal regulation in a small Canadian Inuit community, and examines the techniques by which time discipline is enacted and enforced. In the recent past, it was common for people in Inuit communities north of the Arctic Circle to become turned-around or "backwards" in their temporal orientation during mid-winter and mid-summer. New local norms of time discipline have marginalized this practice. Furthermore, current local norms support adherence to an arbitrary clock time, that while consistent with traditional values in favour of industry and activity, tend to discourage participation in traditional subsistence activities.